Intermittent abortive reactivation of Epstein-Barr virus during the progression of nasopharyngeal cancer as indicated by elevated antibody levels. (June 2019) - Guo, Xiaoyi; Li, Tingdong; Li, Fugui; Xu, Yarui; Wang, Han; Cheng, Weimin; Tang, Jiabao; Zhou, Guoliang; Chen, Honglin; Ng, Munhon; Ji, Mingfang; Ge, Shengxiang; et al.
Highlights: Systematic analysis of antibodies specific to different life cycle EBV antigens. 99 (36.3%) early stage (stage I&II) NPC cases for analysis. Correlation between antibody level and progression of NPC, especially tumour size. Intermittent abortive reactivation of EBV during the progression of NPC. Abstract: The development of nasopharyngeal carcinoma (NPC), a common cancer in Southeastern Asia, is closely associated with Epstein-Barr virus (EBV) infection; however, the aetiological role of EBV in NPC pathogenesis remains enigmatic. The life cycle of EBV in NPC patients is defined as latency II, while the antibodies specific to lytic phase proteins, as well as lytic genes, were highly expressed in NPC patients. The correlation between antibody levels and the progression of NPC has been reported in some studies; however, most of these studies focused on IgA antibodies, and the results in different articles were not consistent. In this study, we concurrently determined the levels of IgA and IgG antibodies specific to six purified recombinant EBV antigens associated with different replication statuses of EBV: EBNA1 associated with latency II; the non-structural antigens Zta, TK, EA-D and EA-R associated with immediate-early and early lytic phases; and the EBV matrix protein VCA p18, which is involved in late lytic phase. Levels of antibodies specific to immediate-early and early antigens were correlated with the tumour progression, especially tumour size. The levels of antibodies specific to some lytic phase antigens were also correlated with lymph node inclusion and metastasis. However, the antibody specific to the latency II antigen EBNA1 was not correlated with either tumour size or metastasis. Consistent with previous transcriptome studies, the results suggested both the expression of lytic phase genes at the protein level and the intermittent reactivation of EBV in NPC patients.